Cathepsin F of Teladorsagia circumcincta is a recently evolved cysteine protease. (October 2020) - Sloan, Sarah; Jenvey, Caitlin; Cairns, Callum; Stear, Michael
Parasitic cysteine proteases are involved in parasite stage transition, invasion of host tissues, nutrient uptake, and immune evasion. The cysteine protease cathepsin F is the most abundant protein produced by fourth-stage larvae (L4) of the nematode Teladorsagia circumcincta, while its transcript is only detectable in L4 and adults. T. circumcincta cathepsin F is a recently evolved cysteine protease that does not fall clearly into either of the cathepsin L or F subfamilies. This protein exhibits characteristics of both cathepsins F and L, and its phylogenetic relationship to its closest homologs is distant, including proteins of closely related nematodes of the same subfamily.